Validation The theory of the Non-worship Ayat Al-Ahkam ineffectiveness - seyed abdorrasul hoseynizadeh; Rahim Haseli; fatemeh firoraghi (پژوهش نامه معارف قرآنی, 2020)
The effectiveness or ineffectiveness of non-Quranic rulings is one of the issues that have been explored from various angles in the present era. The theory of rational manuscripts is one of these theories which, by believing in the ineffectiveness of the aforementioned decrees in the present age, indicate the immortality of the Qur'an, and rules the replacement of these rulers by decrees derived from definite or doubtful reason. Dividing the divine judgments-as one of the fundamentals of the theory-seeks to prove the ineffectiveness of the verses of Allah. Therefore, the following is validated by a descriptive-analytic method in the preceding research, as a result of which these divisions are faced with important problems, the most important of which can be in the titles of "failure", "definition ambiguity" , "Ambiguity of limitations" and "the existence of quantitative and qualitative inconsistencies in the essence of the hypothesis"; the difficulties that we must add to the opposition to the many intrinsic arguments must be made clearer in order to discredit the aforementioned theory